The Characteristics of Vietnamese Collective Living Quarters - From the Foundational Concepts to Changes - Duong Tat Thanh, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
The development of the modern urban city has always been accompanied by problems related to the urban planning and adjustment of its internal infrastructure. All the planning and construction of cities are associated with a specific plan, also there are some theories of planning and housing sector included. The theoretical system is built and adjusted, applied from the practice of model designs or pilot designs then adopted and used by experts of different countries. However, each region has different political, socio-cultural, economic, and environmental conditions; therefore, applying such theoretical systems will have active adjustments based on separate circumstances and contexts. Throughout the history of urban development of many countries in the world, the characteristics of the model “group of houses” have been used thoroughly and effectively of social issues and seen not only as a situational but also long-term approach to the development of cities. From the Neighbourhood Unit concept to the Collective living quarters concept then applied in Vietnam - although there is a certain adjustment - still shows the visions of designers and intentions as well as the look for deeply social value. To Vietnam’s situation, in particular, the collective living quarters concept is considered an ideal model and a changing step not only in the history of architecture but also the social development history in general, representing a whole generation of humanity with socialism, closely attached to the historical context of Vietnam.Received 18th December 2021; Revised 12th February 2022; Accepted 20th March 2022